Algebrization of Nonautonomous Differential Equations - Alcorta García, María Aracelia; Frías Armenta, Martín Eduardo; Grimaldo Reyna, María Esther; López González, Elifalet (2015)
Given a planar system of nonautonomous ordinary differential equations,